Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/1477-9552.12295
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Migration, Remittances and Public Transfers on Technology Adoption: The Case of Cereal Producers in Rural Kenya

Abstract: Risk and liquidity constraints are major obstacles to the adoption of modern technologies in many rural African countries. Migration and remittances can help rural households overcome these constraints and increase the adoption of modern technologies. We analyse the impact of migration, remittances and government transfers on the adoption of improved seeds in rural Kenya. Using data from the World Bank, two stage least-squares estimates show that both migration and remittances positively affect the adoption of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…However, the marginal effect of PM‐JDY payments indicates that an additional INR 1000 in PM‐JDY benefits increased the likelihood of purchasing seeds by about 12% immediately after receiving the assistance. Our finding is consistent with other studies (Jack, 2013; Tshikala et al, 2019). Last, Panel C reports the marginal effects of program payments on the procurement of fertilizers and pesticides.…”
Section: Resultssupporting
confidence: 94%
“…However, the marginal effect of PM‐JDY payments indicates that an additional INR 1000 in PM‐JDY benefits increased the likelihood of purchasing seeds by about 12% immediately after receiving the assistance. Our finding is consistent with other studies (Jack, 2013; Tshikala et al, 2019). Last, Panel C reports the marginal effects of program payments on the procurement of fertilizers and pesticides.…”
Section: Resultssupporting
confidence: 94%
“…Currently, numerous studies have found that remittance inflows are another potential source that increases environmental degradation in various economies of the world. The remittance inflows have a vital source of foreign capital which significant positive influence on numerous economies outcomes for example financial development (Olayungbo and Quadri 2019), foreign direct investment (Basnet and Upadhyaya 2014), technological innovation (Tshikala et al 2019), and economic growth (Chowdhury 2016), which are measured as an important indicator for environmental sustainability. The BRICS countries have received a remittance of approximately 1.10$ trillion in 2017; these economies have top remittance receiver's economies among developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…National household survey data from Kenya suggest that low-income households are the greatest beneficiaries of cash remittances. While the remittances literature in Kenya generally focuses on the investment of remittances in agricultural production, there is more general evidence that a primary use of cash remittances in rural areas is food purchasing [33]. One study, for example, argues that many rural dwellers in Africa buy more food than they sell and, as net food buyers, are from low-income households who depend on remittances to access purchased food [34].…”
Section: Introductionmentioning
confidence: 99%